Controversies Involving the Systemic Treatment for Metastatic Prostatic Cancer - Eisenberger, Mario (Revista Brasileira de Cancerologia, 2023)
In the United States, 1987 estimates of cancer incidence by site indicate that prostatic cancer is equal to lung cancer as the first in incidence in adult males. Over 90,000 new cases are diagnosed and between 25-30,000 patients die of this disease each year. While early prostatic cancer is a surgically curable disease, the majority of patients present with widely metastatic cancer, where the main objective of treatment is palliation.